Case report: Severe sinus tachycardia as a leading manifestation of systemic lupus erythematosus flare - Ashour, Anas A.; Mansour, Shafik; Talal Basrak, Mohamad; Altermanini, Mohammad; Sawaf, Bisher; Atta, Mohamed A.; Habib, Mhd Baraa (Frontiers in Medicine, 2023)
Systemic lupus erythematosus (SLE) is known to have various cardiac manifestations, including arrhythmias and tachycardia. However, it is rare to encounter severe sinus tachycardia as a presenting feature in patients with SLE.Herein, we present a case of a 32-year-old Filipino female with a history of recurrent hospital admissions due to palpitations and uncontrolled tachycardia.Despite trying various symptomatic treatments, her symptoms remained persistent.Ultimately, the patient was diagnosed with SLE during her hospital stay.Eventually, her symptoms improved after initiating steroids. In conclusion, severe sinus tachycardia could be an unusual presentation of SLE that physicians should consider.